2016
DOI: 10.1007/s12035-016-9845-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 Regulates the Expression of BACE1 in the Hippocampus Under Chronic Cerebral Hypoperfusion

Abstract: Chronic cerebral hypoperfusion (CCH) is a high-risk factor of Alzheimer's disease (AD). MicroRNAs (miRNAs) are ideal mediators of hypoxic stress responses to facilitate cellular adaptation to long-term hypoxia. MiR-124 is a kind of nervous system-specific miRNAs, and one of its target genes is β-site amyloid precursor protein cleaving enzyme 1 (BACE1). In the present study, miR-124 was found to be inhibited all the time from early to late stage of cerebral hypoxia accompanying with the upregulation of BACE1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Similar results were obtained with intrahippocampal injections of amyloid ␤ peptide. Consistent with previous reports, activation of EPAC effectively attenuated miR-124 levels, but the magnitude at which EPAC activation or the increased EPAC expression affects BACE1 was not determined (1193).…”
Section: Alzheimer's Diseasesupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were obtained with intrahippocampal injections of amyloid ␤ peptide. Consistent with previous reports, activation of EPAC effectively attenuated miR-124 levels, but the magnitude at which EPAC activation or the increased EPAC expression affects BACE1 was not determined (1193).…”
Section: Alzheimer's Diseasesupporting
confidence: 89%
“…Although tempting to conclude that the additive reduction of miR-124 by decreased cerebral blood flow along with amyloid ␤ peptide elevation may signify some sort of tipping point in disease progression, further analysis is required to fully understand this process. This is based on the conclusion that BACE1 expression is not solely regulated by miR-124 since overexpression of the microRNA was unable to completely block BACE1 induction in response to hypoxia or amyloid ␤ peptide insults (1193). Although the precise mechanism for miR-124 remains elusive, chronic cerebral hypoperfusion and amyloid ␤ peptide both promote suppression of miR-124 and may, in part, augment BACE1 expression through a positive feedback mechanism; however, still to be determined is the more complex network regulating the ␤-secretase.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…On the other hand, Epac/Rap1 can regulate the toxic cleavage of APP. In the presence of Aβ or hypoxia, Epac/Rap1 is involved in miR-124 inhibition [ 58 ]. miR-124 regulates BACE1 secretase mRNA expression and protein levels, which is the enzyme responsible for the β cleavage of APP.…”
Section: Small Gtpases Of the Ras Familymentioning
confidence: 99%
“…CCH causes neurological damage in a long period of time that eventually ends up with a progressive cognitive and neurological dysfunction (2,3). It is related to persistent decrease in cerebral blood fl ow (CBF) due to neurovascular dysfunction, consequently leading to cerebral ischemia (32). The current study demonstrated not only CCH-induced mechanism of neurodegeneration in part, but also the neuroprotective potential of EP for CCH type of ischemic injury.…”
Section: Discussionmentioning
confidence: 61%